Lack of chemokine (C-C motif) ligand 3 leads to decreased survival and reduced immune response after bacterial meningitis. (November 2018) - Aust, Vanessa; Kress, Eugenia; Abraham, Stephanie; Schröder, Nicole; Kipp, Markus; Stope, Matthias B.; Pufe, Thomas; Tauber, Simone C.; Brandenburg, Lars-Ove
Highlights: CCL3 lack resulted in an ineffective immune response against bacteria in the brain. There is less neutrophils infiltration into the CNS. Decrease of banded neutrophils in the blood of infected CCL3 mice. CCL3-KO mice showed an decreased cytokine expression profile after infection. Abstract: Pneumococcal meningitis, caused by Streptococcus pneumoniae, is the most common type of bacterial meningitis. The clinical management of this disease has been challenged by the emergence of multidrug-resistant Streptococcus pneumoniae, requiring the urgent development of new therapeutic alternatives. Over the course of bacterial meningitis, pathogen invasion is accompanied by a massive recruitment of peripheral immune cells, especially neutrophil granulocytes, which are recruited under the coordination of several cytokines and chemokines. Here, we used chemokine (C-C motif) ligand 3 ( Ccl3 )-deficient mice to investigate the functional role of CCL3 in a mouse model of pneumococcal meningitis. Following intrathecal infection with Streptococcus pneumoniae Ccl3 -deficient mice presented a significantly shorter survival and higher bacterial load than wildtype mice, paralleled by an ameliorated infiltration of neutrophil granulocytes into the CNS. Blood sample analysis revealed that infected Ccl3 -deficient mice showed a significant decrease in erythrocytes, hemoglobin and hematocrit as well as in the number of banded neutrophils. Moreover, infected Ccl3 -deficient mice showed an altered cytokine expression profile. Glial cell activation remained unchanged in both genotypes. In summary, this study demonstrates that CCL3 is beneficial in Streptococcus pneumoniae -induced meningitis. Pharmacological modulation of the CCL3 pathways might, therefore, represent a future therapeutic option to manage Streptococcus pneumoniae meningitis.